THE INFLUENCE OF TRANSACTIONAL LEADERSHIP STYLE ON EMPLOYEE TURNOVER PT LION EXPRESS - Lucia Ratu Persia; Agung Surya Dwianto (LP2M Universitas Bina Bangsa, 2024)
Objective. This study aims to evaluate and examine the effect of transactional leadership style on employee turnover at PT Lion Express. Method. The research method used is a quantitative approach, where data collection is done through questionnaires. The population of this study consisted of former employees at PT Lion Express, which amounted to 73 individuals. The sample was taken using the saturated sampling method. The data obtained were analyzed using SPSS version 25 software, with descriptive analysis methods and hypothesis testing in the form of regression analysis. Results. This research shows that transactional leadership style has a significant influence on employee turnover of PT Lion Express. This study also shows that the null hypothesis is rejected and the alternative hypothesis is accepted. The results of this study confirm that transactional leadership style has a significant positive effect on employee turnover. Implication. The findings provide valuable insights for the management of PT Lion Express, who may consider evaluating and possibly changing the applied leadership style to reduce employee turnover rate as well as against companies with similar leadership styles.